PENGARUH SUBSTITUSI RESIDIUM CATALYTIC CRACKING DAN LIMBAH PABRIK BATU TERHADAP NILAI CBR TANAH LEMPUNG EKSPANSIF - Hastuti, Yulia; Silitonga, Estina Nurma; Dewi, Ratna (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
In planning road construction, a pavement design is connected with the soil CBR value. Soil is the road foundation that needed to be considered. Problems which were usually caused by soil were properties or the content of such poor soil of high plasticity, high dry bulk density, small shear-strength soil, big thriving and shrinking, and also a low CBR value. Therefore, the relevancy of doing the research was to improve the strength of expansive clay soils, one of which was the chemical stabilization or adding certain chemicals, causing a chemical reaction. To overcome the existing problems in the expansive clay soils research conducted using Residium Catalytic Cracking and Stone Factory Waste as stabilization material. The purpose of this study was to determine the effect of substituting Residium Catalytic Cracking with factory waste rock to the value of CBR (California Bearing Ratio) on expansive clay.  Expansive clay soil samples was taken from the area of ​​Tanjung Api-api Km.27 Palembang, whereas samples of Catalytic Cracking Residium was taken from PT. Pertamina RU III, Palembang and Stone Factory Waste was taken from Lengot, sub-district of Jayapura, East Oku Regency (OKUT). Variation of mix were Catalytic Cracking Residium 0%, 2%, 4%, 6% and stone factory waste 0%, 20%, 25%, 30% with treatment period 0, 7 and 14 days. The results showed that the stabilizing agent of Residium Catalytic Cracking could increase the value of CBR expansive clay soil while the addition of the Stone Factory Waste lower the value of CBR expansive clay. From the optimization results of CBR value, the best composite were 6% Catalytic Cracking Plant and 0% Stone Factory Waste with 4.1% CBR value and the percentage transformation in the CBR value 124.044%.